Application hybrid GSAPSO Technique for AGC in Inter Connected Power System with Generation Rate Constant - Pabitra Mohan Dash, Asini Baliarsingh, Sangram Keshori Mohaptra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An attempt has been taken in this work to effectively implement the combination of GSA and PSO (hGSA-PSO) technique towards AGC in two-area inter-connected power systems with generation rate constraint (GRC) is considered. For the design and analysis, a initial attempt has been taken to optimize parameters of proportional-integral-derivative (PID) controller in two area non-reheat thermal power system employing GSA and hGSA-PSO algorithm with ITAE objective function. A sensitivity studies carried out for the robustness of the system by changing the operating condition and variation of the parameter and generation rate constant (GRC= ±0.05 and ±0.025) is considered. The performances of the proposed controller has been evaluated with those of some previously published optimization techniques such as GA and BOFA based optimized controller parameters for the same power system. This study of the present work is extended to two area multi sources power system to test the robustness analysis of the system by comparing the hGSA-PSO optimized to PI controller with same structure of system by selecting with and without GRC for showing the dynamic performance analysis of the system in term of settling time and overshoot.